Extraction Cellulose From Rice Husk - Muhammad Arham Yunus (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Abstract. Cellulose from rice husk has been successfully synthesized. Rice husk is an abundant agricultural waste and has a high cellulose content. Bioconversion of rice husk into cellulose begins with the stages of delignification and bleaching. The resulting cellulose was characterized using FTIR and XRD. The IR spectra show a strong absorption peak at 3444.87 cm− 1 which is associated with stretching vibrations O − H (hydrogen bonds between molecules), absorption peaks at 1033.85 cm− 1 are identified as stretching C − O − C which is β bond −1,4 glycosidic from cellulose. XRD shows the particle size of cellulose which is 3.44 nm and has crystallinity of 58.73%. These results indicate that cellulose from rice husk has good characteristics.              Keywords: Rice Husk, Cellulose, FTIR, XRD